Jerry & Marge go large [videorecording (DVD)] - Copeland, Brad; Monaco, Jake; Hannan, Mary Claire; Alberti, Maryse; Cranston, Bryan, 1956-; Bening, Annette; Wilmore, Larry; Wilson, Rainn, 1966-; Camp, Anna, 1982-; Harada, Ann; Manohar, Cheech; McDorman, Jake, 1986-; et al. (Paramount, 2022)
When retiree Jerry Selbee discovers a mathematical loophole in the Massachusetts lottery, he and his wife Marge go on an exciting multi-million dollar winning spree to revive their small Michigan town. But when a selfish college student cheats the system, Jerry must find a way to make the game fair for all.